Correlation between serum Visfatin and cognitive impairment in maintenance hemodialysis patients - Wang Xiao-qi; Liu Cong-hui; Ma Ye-ping; Cao Qian-ying; Shao Feng; Li Zhong-xin (Linchuang shenzangbing zazhi)
ObjectiveTo study the correlation between serum Visfatin and cognitive impairment （CI） in maintenance hemodialysis （MHD） patients.MethodsIt was a cross-sectional study. From July 1， 2023 to January 31， 2024， baseline characteristics of MHD patients treated in the Beijing Luhe Hospital，Capital Medical University were collected. Serum level of Visfatin was evaluated using fasting blood samples. Cognitive function was assessed using the Montreal cognitive assessment scale （MoCA）. According to the results of MoCA， the patients were divided into cognitive impairment （CI） group and non-CI group. Clinical characteristics were compared between groups. Multivariate logistic regression was employed for analyzing the independent influencing factors for CI. Receiver operating characteristic （ROC） curve was used to analyze the predictive value of influencing factors for CI in MHD patients.ResultsTotally 146 MHD patients were enrolled in this study and divided into non-CI group （n=46） and CI group （n=100）. Compared to the non-CI group， patients in the CI group had significantly older age ［66.00（57.25，71.00）years vs 45.50（40.00，56.25）years］， higher proportion of diabetes （56% vs 32.6%）， Visfatin level ［13.35（7.68，24.68）μg/L vs 7.46（4.46，14.07）μg/L］， blood sugar ［（11.13 ± 5.34）mmol/L vs （9.17 ± 4.46）mmol/L］， body mass index ［24.29（21.24，26.21）kg/m2 vs 21.36（19.94，24.85）kg/m2］， and C-reactive protein［（16.60 ± 23.37）mg/L vs （8.24 ± 10.41）mg/L］ （P<0.05）. Patients in the CI group had significantly lower education years［9.00（6.00，9.00）years vs 12.00（9.00，12.75）years］， albumin （Alb）［40.35（37.70，42.18）g/L vs 42.15（40.28，44.58）g/L］， serum creatinine ［731.00（632.75，876.00）μmol/L vs 951.00（828.75，1102.50）μmol/L］， blood sodium ［136.5（135.0，138.0）mmol/L vs 137.5（136.0，139.0）mmol/L］， and blood phosphorus ［（1.68 ± 0.52）mmol/L vs（1.90 ± 0.57）mmol/L］ than non-CI group （P<0.05）. Multivariate logistic regression analysis showed that increasing age， high Visfatin level， low education level and Alb level were independent risk factors for CI in MHD patients. ROC curve showed that the area under the curve （AUC） of Visfatin for predicting CI in MHD patients was 0.714 （P<0.01）， with the sensitivity of 71.7% and the specificity of 75.0%， which had high predictive value. When Visfatin， Alb， age and education level were combined， the AUC for predicting CI was 0.87， the sensitivity was 78.0% and the specificity was 84.8% （P < 0.01） which performed better in the predictive value than any single indicator.ConclusionFor MHD patients， high Visfatin level is an independent risk factor for CI， which may become a biological indicator for predicting CI.